Impact of using podcasts on students learning motivation - Irmadel Aurelliana; Syifa Syahfiana Nugraha (Universitas Pendidikan Indonesia, 2022)
A podcast is a media file or digital audio to be specific, which can be published regularly through the internet in a particular format, such as mp3 formats. Podcast is also widely used, and the education field is not an exception. During the pandemic state that is happening right now, the education process is required to continue, so a Distance Learning policy is issued, which requires all people, including students, to stay at home as a way to prevent transmission of the virus through a circular by the Minister of Education and Culture that stated in law number 3 of 2020 regarding the prevention of Covid-19. This distance learning policy requires educators to be able to choose suitable learning media. In this research, the researcher uses an interview method with the Mahad Abu Aziz elementary school teacher. The results showed that podcasts as a learning media received a good response from the students. Podcasts can be effectively used in the learning process only if the educators have good speaking ability, including good intonation, and can create a pleasant situation in their audio presentation. In conclusion, podcast as a learning media receives excellent feedback from students because it is considered easy to use and works better, especially in Language lesson.